PENGARUH PENGETAHUAN KURIKULUM 2013 TERHADAP KOMPETENSI PROFESIONALISME GURU KELAS SD/MI SE-KECAMATAN SINJAI BARAT - Selfiana; Yahdi, Muhammad; Nursalam (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to determine the effect of 2013 curriculum knowledge on the professional competence of SD / MI class teachers in West Sinjai District. This study involved two variables, namely the independent variable, namely 2013 curriculum knowledge, while the dependent variable was teacher professional competence. This quantitative research uses ex-post facto research and a simple linear regression research design. The population in this study were all SD / MI class teachers in the West Sinjai District totaling 180 people. While the sample in this study were 36 people using cluster sampling technique. The instruments used in this study were questionnaires and documentation. The data analysis technique used is descriptive statistics and inferential statistics. The results of the research from descriptive statistics obtained that the average value of the 2013 curriculum knowledge for SD / MI class teachers in West Sinjai District was in the moderate category, namely 72.22%, while the results of the professional competence of SD / MI class teachers in West Sinjai District were at medium category, namely 52.78% and inferential statistics obtained (tcount) = 18.848 while (ttable) = 2.032 for a significance level of 0.05%. Because tcount is greater than ttable, it can be concluded that H0 is rejected and H1 is accepted, so it is said that 2013 curriculum knowledge has an effect